Acute supplementation with blackcurrant extracts modulates cognitive functioning and inhibits monoamine oxidase-B in healthy young adults. (August 2015) - Watson, Anthony W.; Haskell-Ramsay, Crystal F.; Kennedy, David O.; Cooney, Janine M.; Trower, Tania; Scheepens, Arjan
Highlights: We assess the effects of two blackcurrant extracts, a Juice and a freeze dried powder. Cognitive outcomes, mood, autonomic measures, monoamine tone, and anthocyanin bioavailability to plasma were assessed. This is the first illustration of a cognitive benefit of acute blackcurrant supplementation in healthy young humans. The first description of a clinically significant inhibition of MAO-B and MAO-A using a commonly consumed fruit. Degree of processing and blackcurrant cultivar used substantially altered the neuroendocrinological and cognitive benefits. Abstract: The consumption of berry fruits engenders a number of benefits in animal models, including improvements in cognitive performance, slowing of cognitive decline during natural ageing, and neuroprotection. These findings, along with limited human epidemiological evidence, suggest a potential role for the consumption of berry fruit polyphenols in improving human cognitive performance. The current study assessed the effects of two blackcurrant extracts on cognitive outcomes, mood, autonomic measures, peripheral and central monoamine tone, and anthocyanin bioavailability to plasma. A randomised, double-blind, placebo-controlled, crossover study was conducted using 36 healthy young participants (18–35 years). Findings from the intervention illustrate a cognitive benefit of acute blackcurrant supplementation in healthy young humans and the first description of a clinically significant inhibition of monoamine oxidase-B and monoamine oxidase-A using a commonly consumed fruit. These data also illustrate that compounds other than anthocyanins may be responsible for the observed in vivo MAO inhibition and that the degree of processing and the cultivar of blackcurrant fruit used substantially alter the neuroendocrinological and cognitive benefits conveyed.